144:poster Quality of pandemic priority setting in the U.S. (28th April 2022) - Noorulhuda, Mariam; Danis, Marion; Sullivan, Connor; Velez, Marcela; Kapiriri, Lydia; Goold, Susan
Abstract : Priority setting during public health emergencies presents an enormous challenge for federal and state decision makers in the U.S. Objectives: We describe the degree to which U.S. priority setting adheres to established quality indicators and explore relationships between such indicators and states' demographic characteristics. Methods: Data includes the U.S. COVID-19 preparedness and response plan of January 2021 and individual state plans. Purposive sampling of 22 states from multiple geographic regions considered total population, % rural residents, income per capita, health ranking, and political leanings. State plans were sought online and using multiple contacts with state health and emergency preparedness departments. We analyzed plans using a tool based on an established framework of quality indicators to evaluate priority setting, for example principles and criteria, stakeholder and public participation, publicity and accountability. Results: The national plan included 7 of 20 quality parameters, including attention to at-risk populations, a comprehensive list of resources and interventions to which priority setting would apply, publicity, and the use of (and efforts to improve) evidence for priority setting decisions. The US plan describes the importance of 'engag[ing] the American people' and various stakeholders to inform the federal response. Enforcement, accountability, incentives, and assessment of impact were not identified in the plan. We obtained pandemic plans from 4 states and documents from 6 states that, while not explicitly labelled as pandemic plans, include priority setting. Analysis is in process; we expect to present results for 4-10 states. Discussion: The US plan's consideration of various scarce resources, public engagement, and equity concerns recognizes the disproportionate impact of COVID-19 among racial and ethnic minorities and low-income communities. However, its lack of accountability and assessment of impact on outcomes may hinder achievement of goals. Difficulty finding and obtaining state plans suggests a lack of publicity and transparency.